Characterization of global research trends and prospects on platinum-resistant ovarian cancer: a bibliometric analysis - Duan, Yuanqiong; Zhang, Peixuan; Zhang, Tianyue; Zhou, Lu; Yin, Rutie (Frontiers in Oncology, 2023)
Background: In the last decades, growing attention has been focused on identifying effective therapeutic strategies in the orphan clinical setting of women with platinum-resistant ovarian cancer (PROC), generating thousands of original articles. However, the literature involving bibliometric analysis of PROC has not been published yet. Objective: This study hopes to gain a better understanding of the hot spots and trends in PROC by conducting a bibliometric analysis, as well as identify potential new research directions. Methods: We searched the Web of Science Core Collection (WOSCC) for PROC-related articles published between 1990 and 2022. CiteSpace 6.1.R2 and VOS viewer 1.6.18.0 were primarily utilized to evaluate the contribution and co-occurrence relationships of various countries and regions, institutes, and journals and to identify research hotspots and promising future trends in this research field. Results: A total of 3,462 Web of Science publications were retrieved that were published in 671 academic journals by 1135 authors from 844 organizations in 75 countries and regions. The United States was the leading contributor in this field, and the University of Texas MD Anderson Cancer Center was the most productive institution. Gynecologic Oncology was the most productive journal, while the Journal of Clinical Oncology was the most cited and influential. Co-citation cluster labels revealed the characteristics of seven major clusters, including synthetic lethality, salvage treatment, human ovarian-carcinoma cell line, PARP inhibitor resistance, antitumor complexes, folate receptor, and targeting platinum-resistant disease. Keywords and references burst detection indicated that biomarkers, genetic and phenotypic changes, immunotherapy, and targeted therapy were the most recent and most significant aspects of PROC research. Conclusion: This study conducted a comprehensive review of PROC research using bibliometric and visual techniques. Understanding the immunological landscape of PROC and identifying the population that can benefit from immunotherapy, especially in combination with other therapeutic options (such as chemotherapy and targeted therapy), will continue to be the focal point of research.